Congenital Rubella Syndrome Surveillance in South Africa Using a Sentinel Site Approach: A Cross-sectional Study. (8th September 2018) - Motaze, Nkengafac Villyen; Manamela, Jack; Smit, Sheilagh; Rabie, Helena; Harper, Kim; duPlessis, Nicolette; Reubenson, Gary; Coetzee, Melantha; Ballot, Daynia; Moore, David; Nuttall, James; Linley, Lucy; et al.
Abstract: Background: Congenital rubella syndrome (CRS) includes disorders associated with intrauterine rubella infection. Incidence of CRS is higher in countries with no rubella-containing vaccines (RCV) in their immunization schedules. In the World Health Organization African region, RCVs are being introduced as part of the 2012–2020 global measles and rubella strategic plan. This study aimed to describe the epidemiology of confirmed CRS in South Africa prior to introduction of RCVs in the immunization schedule. Methods: This was a descriptive study with 28 sentinel sites reporting laboratory-confirmed CRS cases in all 9 provinces of South Africa. In the retrospective phase (2010 to 2014), CRS cases were retrieved from medical records, and in the prospective phase (2015 to 2017) clinicians at study sites reported CRS cases monthly. Results: There were 42 confirmed CRS cases in the retrospective phase and 53 confirmed CRS cases in the prospective phase. Most frequently reported birth defects were congenital heart disease and cataracts. The median age of mothers of CRS cases was 21 years in the retrospective phase (range: 11 to 38 years) and 22 years in the prospective phase (range: 15 to 38 years). Conclusion: Baseline data on laboratory-confirmed CRS will enable planning and monitoring of RCV implementation in the South African Expanded Programme on Immunization program. Ninety-eight percent of mothers of infants with CRS were young women 14–30 years old, indicating a potential immunity gap in this age group for consideration during introduction of RCV. Abstract : Sentinel site surveillance for congenital rubella in South Africa identified 95 cases from 2010 through 2017. Mothers of infants with congenital rubella were 14–38 years old. This information will inform planning of rubella vaccine introduction in the region.